Evaluation of sensorless VF-MRAS and FOC-MRAS of IM electrical drive system - Diop, Moustapha; Kebe, Abdoulaye; Gueye, Ibrahima (Institute of Advanced Engineering and Science, 2025)
This paper evaluates the performance of sensorless vector and scalar control methods, namely field-oriented control-based model reference adaptive system (FOC-MRAS) and voltage frequency-based model reference adaptive system (VF-MRAS), applied to an induction motor (IM) driven by a space vector modulation inverter. In motorized systems, conventional control methods use mechanical sensors, which can be cumbersome and costly. To overcome these limitations, sensorless control techniques based on speed estimation have been introduced. In this paper, MRAS-based sensorless speed control for IM drives using rotor flux is used. This adaptive system uses a reference model based on rotor flux and implements closed-loop control. The estimated speed derived from the current and voltage models is compared to the desired speed and adjusted by the proportional-integral (PI) controllers. The performances of the approaches are evaluated in terms of speed regulation and minimization of electromagnetic torque and rotor flux ripples, through a comparative analysis of sensor and sensorless controls under various operating conditions, including variable loads and speed reversal. The simulation results obtained, using consistent criteria for both methods, confirm the effectiveness of sensorless control.